Acute morphine blocks spinal respiratory motor plasticity via long‐latency mechanisms that require toll‐like receptor 4 signalling. (6th July 2021) - Tadjalli, Arash; Seven, Yasin B.; Sharma, Abhisheak; McCurdy, Christopher R.; Bolser, Donald C.; Levitt, Erica S.; Mitchell, Gordon S.
Abstract : Key points: While respiratory complications following opioid use are mainly mediated via activation of mu opioid receptors, long‐latency off‐target signalling via innate immune toll‐like receptor 4 (TLR4) may impair other essential elements of breathing control such as respiratory motor plasticity. In adult rats, pre‐treatment with a single dose of morphine blocked long‐term facilitation (LTF) of phrenic motor output via a long‐latency TLR4‐dependent mechanism. In the phrenic motor nucleus, morphine triggered TLR4‐dependent activation of microglial p38 MAPK – a key enzyme that orchestrates inflammatory signalling and is known to undermine phrenic LTF. Morphine‐induced LTF loss may destabilize breathing, potentially contributing to respiratory side effects. Therefore, we suggest minimizing TLR‐4 signalling may improve breathing stability during opioid therapy. Abstract: Opioid‐induced respiratory dysfunction is a significant public health burden. While respiratory effects are mediated via mu opioid receptors, long‐latency off‐target opioid signalling through innate immune toll‐like receptor 4 (TLR4) may modulate essential elements of breathing control, particularly respiratory motor plasticity. Plasticity in respiratory motor circuits contributes to the preservation of breathing in the face of destabilizing influences. For example, respiratory long‐term facilitation (LTF), a well‐studied model of respiratory motor plasticity triggered by acute intermittent hypoxia, promotes breathing stability by increasing respiratory motor drive to breathing muscles. Some forms of respiratory LTF are exquisitely sensitive to inflammation and are abolished by even a mild inflammation triggered by TLR4 activation (e.g. via systemic lipopolysaccharides). Since opioids induce inflammation and TLR4 activation, we hypothesized that opioids would abolish LTF through a TLR4‐dependent mechanism. In adult Sprague Dawley rats, pre‐treatment with a single systemic injection of the prototypical opioid agonist morphine blocks LTF expression several hours later in the phrenic motor system – the motor pool driving diaphragm muscle contractions. Morphine blocked phrenic LTF via TLR4‐dependent mechanisms because pre‐treatment with (+)‐naloxone – the opioid inactive stereoisomer and novel small molecule TLR4 inhibitor – prevented impairment of phrenic LTF in morphine‐treated rats. Morphine triggered TLR4‐dependent activation of microglial p38 MAPK within the phrenic motor system – a key enzyme that orchestrates inflammatory signalling and undermines phrenic LTF. Morphine‐induced LTF loss may destabilize breathing, potentially contributing to respiratory side effects. We suggest minimizing TLR‐4 signalling may improve breathing stability during opioid therapy by restoring endogenous mechanisms of plasticity within respiratory motor circuits. Key points: While respiratory complications following opioid use are mainly mediated via activation of mu opioid receptors, long‐latency off‐target signalling via innate immune toll‐like receptor 4 (TLR4) may impair other essential elements of breathing control such as respiratory motor plasticity. In adult rats, pre‐treatment with a single dose of morphine blocked long‐term facilitation (LTF) of phrenic motor output via a long‐latency TLR4‐dependent mechanism. In the phrenic motor nucleus, morphine triggered TLR4‐dependent activation of microglial p38 MAPK – a key enzyme that orchestrates inflammatory signalling and is known to undermine phrenic LTF. Morphine‐induced LTF loss may destabilize breathing, potentially contributing to respiratory side effects. Therefore, we suggest minimizing TLR‐4 signalling may improve breathing stability during opioid therapy.